Forkhead box P3: The Peacekeeper of the Immune System. (4th March 2014) - Passerini, Laura; Santoni de Sio, Francesca Romana; Roncarolo, Maria Grazia; Bacchetta, Rosa
Abstract : Ten years ago Forkhead box P3 (FOXP3) was discovered as master gene driving CD4 + CD25 + T cell regulatory (Treg) function. Since then, several layers of complexity have emerged in the regulation of its expression and function, which is not only exerted in Treg cells. While the mechanisms leading to the highly selective expression of FOXP3 in thymus-derived Treg cells still remain to be elucidated, we review here the current knowledge on the role of FOXP3 in the development of Treg cells and the direct and indirect consequences of FOXP3 mutations on multiple arms of the immune response. Finally, we summarize the newly acquired knowledge on the epigenetic regulation of FOXP3, still largely undefined in human cells.